Analytical Modeling of Stresses in the Wall 0f the Human Heart - Aziz Al Alawi (Al-Khwarizmi College of Engineering – University of Baghdad, 2009)
The mechanical function of the heart is governed by the contractile properties of the cells, the mechanical stiffness of the muscle and connective tissue, and pressure and volume loading conditions on the organ. Although ventricular pressures and volumes are available for assessing the global pumping performance of the heart, the distribution of stress and strain that characterize regional ventricular function and change in cell biology must be known. The mechanics of the equatorial region of the left, ventricle was modeled by a thick-walled cylinder. The tangential (circumferential) stress, radial stress and longitudinal stress in the wall of the heart have been calculated. There are also significant torsional shear in the wall during both systole and diastole. In addition there should exist shear stress in the wall of the heart due to action of pressure on the curved surface.